2016
DOI: 10.5812/pedinfect.35919
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cavitary Pulmonary Tuberculosis in Children

Abstract: Background: Cavitary pulmonary tuberculosis (TB) is rare in children. Objectives: The aim of this study was to evaluate the characteristics of cavitary pulmonary TB in children. Patients and Methods: This retrospective study was conducted on 97 children less than 15 years old with pulmonary TB to assess the clinical characteristics and radiographic findings of patients with cavitary lesions. Results: Seven (7%) out of 97 children had cavitary pulmonary TB. All patients were between 13 and 14 years old with a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(18 reference statements)
0
1
1
Order By: Relevance
“…The distribution of radiological ndings observed in this study contrasts with those reported by Hassanzad et al (23) and ndings from Brie ands (24). While our study found a lower prevalence of cavitary lesions (0%), both Hassanzad et al and Brie ands reported the presence of cavitary lesions in a subset of children with pulmonary tuberculosis.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…The distribution of radiological ndings observed in this study contrasts with those reported by Hassanzad et al (23) and ndings from Brie ands (24). While our study found a lower prevalence of cavitary lesions (0%), both Hassanzad et al and Brie ands reported the presence of cavitary lesions in a subset of children with pulmonary tuberculosis.…”
Section: Discussioncontrasting
confidence: 96%
“…According to Brie ands, cavitary pulmonary tuberculosis typically seen in adults, is rare in children, which aligns with our ndings of no cavitary lesions observed in the studied population. However, the presence of cavitary lesions in other studies indicates a higher mycobacterium load, serving as a potential source of infection (24). This discrepancy underscores the variability in disease presentation across different populations and highlights the importance of considering regional and demographic factors when interpreting radiological ndings in pediatric tuberculosis.…”
Section: Discussionmentioning
confidence: 87%